The Producers Role in the Production of Sinden Ngetrend TVRI Yogyakarta - Syifa Rafifah Fauziyah; Muttaqien, Muhammad (Jogjakarta Communication Conference (JCC), 2023)
Sinden Ngetrend LPP TVRI Yogyakarta Program is a cultural arts-themed variety show that showcases the latest social phenomena in a comedy format through the collaboration of puppeteers, musical accompaniments (Pengrawit), and female performers (Sinden). This research aims to examine the role of producers in the production of the Sinden Ngetrend TVRI Yogyakarta using the POAC theory, which stands for Planning, Organizing, Actuating, and Controlling. This study employs a descriptive qualitative method with techniques of interviewing, observation, and documentation, using three sources, namely the Producer, Program Director, and Script Writer, processed through three stages of qualitative data analysis: data reduction, data presentation, and conclusion drawing. The results of this research show that Sinden Ngetrend Producer performs its role by leading and managing production using the POAC theory, makes Sinden Ngetrend an acceptable educational culture show for all groups and attracts artists from Yogyakarta and its surrounding area to be guests or audience.